Nitrogen and Phosphorus Signaling and Transport During Legume–Rhizobium Symbiosis - Ma, Yanlin; Chen, Rujin (Frontiers in Plant Science, 2021)
Nitrogen (N) and phosphorus (P) are the two predominant mineral elements, which are not only essential for plant growth and development in general but also play a key role in symbiotic N fixation in legumes. Legume plants have evolved complex signaling networks to respond to both external and internal levels of these macronutrients to optimize symbiotic N fixation in nodules. Inorganic phosphate (Pi) and nitrate (NO3−) are the two major forms of P and N elements utilized by plants, respectively. Pi starvation and NO3− application both reduce symbiotic N fixation via similar changes in the nodule gene expression and invoke local and long-distance, systemic responses, of which N-compound feedback regulation of rhizobial nitrogenase activity appears to operate under both conditions. Most of the N and P signaling and transport processes have been investigated in model organisms, such as Medicago truncatula, Lotus japonicus, Glycine max, Phaseolus vulgaris, Arabidopsis thaliana, Oryza sativa, etc. We attempted to discuss some of these processes wherever appropriate, to serve as references for a better understanding of the N and P signaling and transport during symbiosis.